Pengembangan Bahan Ajar Berbasis Aktivitas Materi Rangkaian Listrik untuk Meningkatkan Hasil Belajar Siswa Sekolah Dasar - ani wahyuni_123; Siti Aulia Hutagalung (el-Ibtidaiy:Journal of Primary Education, 2021)
Researchers conducted a field study to SD PAB 20, and found problems regarding student learning outcomes that were unsatisfactory in science lessons because there was no activity-based learning process (practicum), learning was still limited in time and media.  Therefore, in this study, researchers made the development of activity-based teaching materials in simple electrical circuit material to improve student learning outcomes, increase creativity and critical nature of students.  Before research into the field, the media created were validated by material experts and design experts.  The results of the material expert validation show 80% and the design expert validation is 92.8%.  From these results it can be classified that teaching materials that have been made are proven to be valid and tested for eligibility for testing to students.  For processing student data through pre and posttest, researchers used the N-Gain formula.  From the average pretest results obtained 46 and posttest results obtained an average of 84. If these values are classified, the final result is 70%. The figure is included in the high criteria.  So it can be concluded that, activity-based teaching materials used, can improve student learning outcomes and foster student creative nature.